Sistemas de produção com culturas graníferas e de cobertura em safrinha - Carvalho, Ícaro Camargo de (2018)
The objective of this work was to evaluate the phytomass production, accumulation and nutrient release and soybean yield in production systems with cover crops in succession to soybean cultivation in dystrophic Oxysol in Rondonópolis - MT. The experiment was conducted during the 2016/17 and 2017/18 harvests at the UFMT, Campus of Rondonópolis, in a randomized complete block design with nine cover cropping systems with four replications. The evaluations were performed immediately before desiccation of management in October of 2016 and 2017, and repeated at 15, 30, 60, 90 and 120 days after desiccation. Crotalaria spectabilis and Urochloa ruziziensis were prominent in the phytomass accumulation. C. spectabilis and U. ruziziensis were prominent in the accumulation of nutrients, with the exception of K, Mg and Cu, in which the sunflower + U. ruziziensis system was highlighted for the first two and maize + C. spectabilis for Cu, in the 2016/17 season. U. ruziziensis was highlighted in the accumulation of macronutrients in the 2017/18 crop. The off season production systems composed of C. spectabilis, maize + C. spectabilis, sunflower + U. ruziziensis, P. glaucum and U. ruziziensis were efficient to increase soybean yield in succession to cover crops in southern of Mato Grosso.